ASSESSMENT OF THE ECOTOURISM POTENTIALS OF OSUN OSOGBO WORLD HERITAGE SITE OSUN STATE, NIGERIA (2014)
Uncontrolled entry into World Heritage Sites (WHS) and other tourism sites may impact negatively on vegetation and wild animal populations, thereby reducing their potential for ecotourism development. Balanced site ecology and conducive socio-economic environment are germane to sustainable ecotourism development. Needed, information on these is not well documented for Osun Osogbo WHS. Therefore, some aspects of site ecology and socio-economic variables were investigated in Osun Osogbo WHS, Nigeria. The study was carried out using three sets of structured questionnaires, personal interview and field surveys. The sets of questionnaire were systematically administered on fifty local residents, randomly administered on 100 tourists and 60% of the WHS staff (50), respectively. Information was obtained on wildlife resources, tourism potentials, managerial challenges and administrative approaches. Within the three vegetation zones in the site: Dry High Forest (DHF), Dry Savanna Forest (DSF) and Riparian Forest (RF), samples of water were taken and nutrient agars were used to isolate their pathogens. Also, three sample plots (30mx30m) were laid in each zone for vegetation survey to determine Diameter at Breast Height (DBH), Basal Area (BA) and volume of trees. Point count and Rodger's methods were used to enumerate birds and terrestrial wildlife, respectively. Data were analysed using descriptive statistics, chi-square and ANOVA at α0.05. Anthropogenic activities identified within the site were farming (37.3%), firewood and medicinal plants collection (20.9%), illegal grazing (17.1%), poaching (10.5%), fishing (9.2%) and crafting (5.0%). In order of importance, income (32.0%), literacy level (26.5%) and tourist’s interest in culture (23.5%) were perceived to impact tourism in the WHS. The modal age group of tourists was 10-20years (40.5%). Tourist's visitation to WHS was found to be dependent on their age (χ2 = 12.97; df = 4; α0.01). Tourists population was observed to fluctuate between 38,000 in 2006 and 63,000 in 2010, while internally generated revenue recorded during these period was between N120, 000:00 and N250, 000:00. Bacteria isolated from the water included: Escherichia coli (8xl04cfu/mL), Salmonella sp. (7.5xl04 cfu/mL), Staphylococus sp. (5.5xl04 cfu/mL), Vibro cholera (7.5xl04 cfu/mL) and Shigella sp. (3xl04 cfu/mL). Absolute density of woody plants was 187 trees/ha. Cola milleni had the highest (18.71/ha) density on the site, while Antiaris toxicaria, Anthodeista dyalonensis, Funtumia elastica and Milicia excelsa had the least with 0.53/ha each. The BA in DHF, DSF and RF were 0.75±1.9m2, 0.82±3.1m2 and 0.15±0.3m2 respectively. Tree volume in DHF (0.92±2.0) m3, DSF (0.41±1.12) m3 and RF (0.13±0.28) m3 were significantly different. The DBH in DHF (22.42±21.6), DS (20.47±25.44) and RF (11.64±7.3) were also significantly different. The study area was covered by luxuriant vegetation types and was mainly inhabited by white throated monkey (Cercopithecus erythrogaster). Sixteen reptiles, 13 avians and 20 other wildlife species were identified in the site with the white throated monkey (Cercopithecus erythrogaster) being the most sighted wild animal. Osun Osogbo world heritage site has high potential for ecotourism development. There was evidence of inadequate management and human pressure. Habitat improvement, enhanced site protection and public awareness campaign were therefore recommended.